Administrative and financial issues of application of the Law of Ukraine "On Amendments to Certain Laws of Ukraine on the Establishment of Educational Institutions by Religious Organizations" by local councils - Шаповал, Р. В. (Право, 2017)
In the article the national legal framework on freedom to profess religious beliefs has been analysed in comparison with the relevant European legislation. The authors have monitored the relationship of the church and the school around the world, including Western Europe. Some legal contradictions and problems on the practical implementation of the Law of Ukraine «On amendments to some laws of Ukraine» (concerning the establishment of the educational institutions by religious organizations) are studied. // У статті проаналізовано національну правову базу щодо свободи сповідування релігійних переконань у порівнянні з відповідним європейським законодавством. Автори спостерігали за взаємовідносинами церкви та школи у всьому світі, включаючи Західну Європу. Вивчено деякі юридичні суперечності та проблеми щодо практичної реалізації Закону України «Про внесення змін до деяких законів України» (щодо створення навчальних закладів релігійними організаціями).
Адміністративні та фінансові питання застосування Закону України «Про внесення змін до деяких законів України щодо заснування релігійними організаціями навчальних закладів» місцевими радами
Keywords: religious organization; education; nonprofit institution; charity; релігійна організація; освіта; некомерційна установа; благодійність